Entre cultura política, memórias e política de identidade: sujeitos históricos em ação Boa Vista - Roraima (1970-1980) - Santos, Raimundo Nonato Gomes dos (2015)
This paper reveals the dynamic of the construction of political identities in the city of Boa Vista, Roraima between the 1970s and 1980s. Having the displacement of traditional identities as an observation reference thought from the political culture perspective, for the political identity , more associated with minorities movements that had the indigenous movement, which begins during this period, as a strong local representative. Its focus is in the position occupied by ordinary people in this process. It has a wide range of documentations as research source: works by memorialists; reports from visitors and executives; official, commercial and alternative newspapers; monuments; individual interviews and; documents from several sources. This paperobserves that the period showed to be adverse to the identity inventions such as: boa-vistense , roraimense , activities which, in some aspects, competed against the national identity strengthened with the implantation of the Federal Territory of Roraima, as well as it was also under the influence of movements originating from abroad which presented itself strongly in the city, such as the Liberation Theology and the environmentalist movement